Allocation Efficiency of Agricultural Sector Resources in Supporting Food Security, Economic Equity, and Regional Self-Reliance in Bireuen Regency - Hakim Muttaqim; Fauzi Fauzi; Muhammad Rizal (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study investigates the efficiency of resource allocation in rice farming to support food security, economic equity, and regional self-reliance in Bireuen District. A mixed-methods approach was employed, integrating quantitative analyses using Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) with qualitative methods comprising in-depth interviews and Focus Group Discussions (FGDs). The data used is primary and secondary data. The results indicate that technical efficiency in rice farming remains relatively low, with average DEA and SFA scores of 0.88 and 0.86, respectively, implying a potential input reallocation of 10–15%. Key determinants of efficiency include farmers’ education, access to formal credit, participation in farmer groups, and proximity to markets. In contrast, limited capital, insufficient technology, and small landholdings (<0.5 ha) were identified as the primary sources of inefficiency. Qualitative findings corroborate the quantitative results, revealing that smallholder farmers are more vulnerable to inefficiency than larger-scale farmers (>1 ha). The study concludes that improving efficiency necessitates targeted policy interventions, including expanding access to microcredit, promoting mechanization, strengthening farmer group institutions, and stabilizing paddy prices. These measures are critical for enhancing food security, reducing economic disparities, and fostering sustainable regional self-reliance in Bireuen District.